Status and organizations theories and cases / Alexander Styhre. - Styhre, Alexander (Palgrave Macmillan, 2022)
This book examines social status as a social mechanism and a social fact that strongly shapes how markets and organizations are regulated, managed, and preserved over time. The first part of this book identifies a number of organizational issues and managerial concerns that can be framed as being a matter of the cognitive perspectives of social actors, and better explained on the basis of such conditions. The second part demonstrates the analytical value of the concept of status in a variety of organizational settings and market contexts. In the three empirical settings, status does play a key role when resources such as legitimacy (in urban development projects), revenues from sales (in video game marketing), and access to venture capital (in life science companies) are distributed. This book summarizes and reviews the academic literature on status and organization studies, as well as providing valuable information for researchers conducting empirical testing. It will be of great interest to students and scholars of Organizations and Social Systems. Alexander Styhre holds the Chair of Organization and Management in the School of Business, Economics and Law at the University of Gothenburg, Sweden. His research interests cover a wide area of research, including innovation management, urban development activities, and institutional, legal, and regulatory changes in the economic system of competitive capitalism.